PREPARATION OF FINANCIAL BOOKKEEPING TO IMPROVE THE FINANCIAL PERFORMANCE OF HOUSEWIVES' UKM GAMPONG SIMPANG EMPAT LHOKSEUMAWE - Muttaqien; Wardhiah; Muhammad Hafizh; Frengki Putra Ramansyah; Cut Zira Maulida (RADJA PUBLIKA, 2024)
Gampong Simpang Empat, located in Banda Sakti Sub-district, Lhokseumawe City, Aceh Province, has people with various livelihoods such as fishermen, farmers, laborers, civil servants, and business actors in the service sector. With the growth in population from 171,163 in 2010 to 190,624 in 2017, the need for financial management for MSME players, including housewives, is increasingly urgent. Bookkeeping is an important process in recording income, cash flow, liabilities, and assets to analyze financial performance, which serves as an evaluation tool for business efficiency and effectiveness in achieving sustainable growth. This service aims to improve the skills of housewives and MSME players in preparing simple financial bookkeeping through economic literacy-based training. The training involves a group learning method with a focus on hands-on practice, from preparation to preparation of financial statements. This type of research uses a quantitative descriptive method with the research population being mothers in Gampong Simpang Empat. Primary data was obtained through a Likert scale-based questionnaire, with random sampling. Data analysis was carried out using regression with the help of SPSS software. The results of this service are expected to have a positive impact on the financial management of MSME actors, especially in recording transactions in a structured manner and separating personal finances from businesses. The outputs of this activity include international journal publications, indexed proceedings, and ISBN-certified reference books. In addition, this research also aims to identify socio-economic factors that affect the income of traditional fishermen in the surrounding area, as a basis for developing more holistic and sustainable solutions. These outputs are designed to achieve technology readiness level (TKT) 3, which is the proof of concept of the research in developing local economic empowerment strategies.